Using the Teaching at the Right Level (TARL) Approach at SMA Negeri 2 Semarang, Independent Curriculum in Physical Education Learning Implementation - Nindyatama, Muhammad Luthfi; Maliki, Osa (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The aim of the Merdeka Curriculum Program is to enhance the learning process. This study aims to investigate the implementation of the Merdeka curriculum in PJOK learning utilizing the Teaching at the Right Level (TaRL) approach at SMA Negeri 2 Semarang in 2024. Materials and Methods. This investigation employs a Qualitative Descriptive research approach. The sources for the study include the Vice Principal for Curriculum, the Vice Principal for Facilities and Infrastructure, Physical Education Subject Teachers, and students from SMA Negeri 2 Semarang. The methodology for this study involves gathering data through observation, documentation, and interviews. Results. SMA Negeri 2 Semarang has adopted the Independent Curriculum starting from the odd semester of the 2022/2023 academic year. In light of numerous challenges and obstacles, the Independent Curriculum at SMA Negeri 2 Semarang has been effectively implemented. It is essential to enhance the facilities and infrastructure in PJOK learning. Conclusion . The findings of the study reveal that the Independent Curriculum has been put into practice at SMA Negeri 2 Semarang starting from the odd semester of the 2022/2023 academic year. The implementation of this curriculum is progressing positively, even in the face of various challenges. Nonetheless, enhancements in the facilities and infrastructure for PJOK learning are essential. To enhance the execution of the Independent Curriculum in PJOK learning at SMA Negeri 2 Semarang, it is advisable to upgrade sports facilities, provide continuous training for educators, carry out regular evaluations, engage parents and the community, and create engaging and pertinent learning materials.